2022
DOI: 10.1038/s41598-022-09987-z
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of differences by parental education in weight-related outcomes in childhood and adolescence in Norway

Abstract: Studies exploring mediators of socioeconomic inequalities in excess weight gain in early-life and subsequent overweight/obesity (OW/OB) among youth are limited. Thus, this study examined the mediating role of prenatal and early postnatal factors and child energy balance-related behaviours (EBRB) in the effects of parental education on (i) excess weight gain from birth to 2 years and (ii) OW/OB at 5, 8 and 14 years. The Norwegian Mother, Father and Child Cohort Study was used to include participants at the ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Different studies have already shown the positive effects of nutritional education on weight in children [15][16][17]. However, our study is the first in Central and Eastern Europe to start education for children at this early age and engage both parents in a very simple and low-cost way using modern technology.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Different studies have already shown the positive effects of nutritional education on weight in children [15][16][17]. However, our study is the first in Central and Eastern Europe to start education for children at this early age and engage both parents in a very simple and low-cost way using modern technology.…”
Section: Discussionmentioning
confidence: 88%
“…A recently conducted study in Norway showed that children of low-educated parents gained more excess weight at two years than children of high-educated parents (total effect, RRTE = 1.06; 95% CI 1.01, 1.10) [16]. Furthermore, children of low-educated parents were more likely to be overweight or have obesity than those of high-educated parents [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, student’s t-tests were used to compare the mean differences in the built environment features of the participants’ residential neighborhoods between the non-overweight and overweight groups. Confounders for the association between neighborhood characteristics and overweight included were individual characteristics such as participant’s ethnicity [ 56 ] and parental education [ 57 ], multivariate analyses of variance adjusting for those covariates were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Confounders for the association between neighborhood characteristics and obesity included were individual characteristics such as participant's ethnicity (56) and parental education (57), multivariate analyses of variance adjusting for those covariates were performed.…”
Section: Statisticsmentioning
confidence: 99%